Testes de software: uma abordagem da atividade de teste software em metodologias ágeis aplicando a técnica behavior driven development em um estudo experimental - Matté, Marcio Angelo (2011)
This paper aims bring together the concepts of software testing in agile methodologies approach through the technique of BDD – Behavior Driven Development. Also part of this document is the contemplation of issues that permeate the theme of software quality.